(Invited) Li-Air Flow Batteries. (10th February 2015) - Chen, X.J.; Shellikeri, Annadanesh; Wu, Qiang; Zheng, J.P.; Hendrickson, Mary A.; Plichta, Edward J.
Abstract : A novel rechargeable Li-air flow battery is demonstrated. It consists of a lithium-ion conducting glass-ceramic membrane sandwiched by a Li-metal anode in organic electrolyte and a carbon nanofoam cathode through which oxygen-saturated aqueous electrolyte flows. It features a flow cell design in which aqueous electrolyte is bubbled with compressed air, and is continuously circulated between the cell and a storage reservoir to supply sufficient oxygen for high power output. It shows high rate capability (5 mA/cm 2 ) and renders a power density of 7.64 mW/cm 2 at a constant discharge current density of 4 mA/cm 2 . By adding RuO2 as a catalyst in the cathode, the battery showed an improved round-trip efficiency (ca. 83%), with the overpotentials of 0.67 V between charge and discharge at a current of 1 mA/cm 2 . A Li-air flow battery using graphite as anode is also demonstrated for several cycles.